Regulatory Arrangement for Shariah Governance Practice of Islamic Banking Institutions in Pakistan: Issues and Challenges - Waqas Farooq; Sahibzada Muhammad Jan Wasi̇m; Ahmad Azam Othman Bin (Hitit İlahiyat Dergisi, 2021)
Shariah governance practice is a vital component of the organizational arrangement of IBIs through which the business affairs of IBIs are examined, certified and monitored. It plays a crucial role to legitimize the business of IBIs. In Pakistan, SBP regulates the practice of Shariah governance through a dedicated department with the aid of its SAC and executes it through Shariah boards of IBIs. Applying descriptive analytical approach, the study has described the current state of Shariah governance practice of IBIs. It is the outcome of the regulatory arrangements in the form of regulatory guidelines, directives, standards and frameworks which have been issued during the last two decades by SBP to standardize the practice of Shariah governance for IBIs in Pakistan. The study highlights the formation of the regulatory arrangement which not only depicts the role of SBP, but it also illustrates the functions of SAC and the responsibilities of Shariah boards at IBIs. The study also attempts to confine the regulatory, advisory and supervisory roles of the SBP, the SAC and the Shariah board of IBIs respectively. An analytical review of the roles of these bodies which are defined through the regulatory arrangements facilitates to discover the loopholes in the current regulatory arrangement for Shariah governance of IBIs. Although, attempts have been made to address the issues in this regard by some writers but in case of Pakistan, the issues are yet to be identified. The study has found that the regulatory arrangement of Shariah governance practice has been constituted significantly by the SBP. However, composition, affiliation and independence of Shariah bodies at central bank and the institutional level are the aspects which pose regulatory issues in the current arrangement. Therefore, the study has discovered some possible solutions for these issues and proposes them for regulatory enhancements. It suggests that the SBP as central regulatory authority should specify regulations over the composition of SAC at SBP level to augment the regulatory and advisory process for Shariah governance practice of IBIs. It recommends that the number of the members at SAC as well as at the Shariah boards of IBIs should be maximized. The two bodies should have additional qualified members especially the number of Shariah qualified members need to be increased. It also proposes that the nomenclature of each body should be defined separately because referring with various names for each body or using their names interchangeably could cause confusion. In addition, the members of SAC and the institutional Shariah boards should be barred from having multiple Shariah boards affiliations through specific regulations. It also recommends that the Shariah boards member must play their supervisory roles independently without any undue influence from the executives. So, a specific set of regulations is required which could guarantee the independence of Shariah boards of IBIs. The proposed recommendations of the study will not only facilitate the regulatory authority to revisit its arrangement and include conclusive measures, but they will also assist the industry to enhance the productivity of their Shariah board members. It will also assist the industry to establish an environment where contribution of the Shariah qualified members and their effective role would strengthen the marketability and credibility of the Shariah governance practice in the Islamic banking industry. Ultimately, a balanced, conclusive and enhanced regulatory arrangement for Shariah governance practice of IBIs would standardize the practice of Shariah governance at the domestic level as well as it could be harmonized with the international best practices of the Islamic banking industry.